Serotype evolution in Western Europe: perspectives on invasive pneumococcal diseases (IPD). (2nd November 2019) - Tin Tin Htar, Myint; Morato Martínez, Jose; Theilacker, Christian; Schmitt, Heinz-Josef; Swerdlow, David
ABSTRACT: Introduction : Epidemiologic trends for IPD have evolved with the introduction of pneumococcal conjugate vaccines into childhood immunization programs. We document the ongoing impact of PCV programs in 15 Western European countries. Areas covered : Data were collected from relevant published observational studies and national surveillance websites from January 2010 through January 2018. In countries using PCV13, the proportion of IPD due to PCV13 serotypes declined significantly (from 60–78% to 8–26%) in children <5 years of age within 5–8 years following vaccine introduction. In countries using PCV10, a marked decrease in PCV10-serotype IPD was reported; however, the proportion of IPD due to PCV13 serotypes remained high at 58–64%, predominantly due to serotypes 19A and 3. Expert opinion : The prevalence of vaccine-type IPD in adults remained high; emerging non-vaccine serotypes such as 8, 12F, 22F, 33F, and 15B/C should be a focus of future vaccine development.